Intracranial Stenting: A Review of the Literature and Recommended Remedies: - Varavipour, Bahman; Gheini, Mohammad-Reza; javanmardi, haniyeh (Galen Medical Journal, 2016)
Intracranial arterial stenosis (ICAS) is one of the main causes of ischemic stroke According to western epidemiological studies, 8-10% of ischemic strokes are attributable to intracranial stenosis. Three modalities of treatment considered for intracranial atherosclerotic disease include; aggressive medical therapy, endovascular revascularization with angioplasty and stent, and extracranial-intracranial bypass surgery. At present, medical management should be the first line of therapy for the most patients with symptomatic intracranial arterial stenosis. Angioplasty and stenting can be considered in some patients that are unstable or have multiple ischemic events in the territory despite aggressive medical management.